The Hollow Umma: A Socio-Epistemic Critique of Mandaville’s Transnational Politics in the Age of Algorithms - Anam, Rifqi Khairul (The Indonesian Islamic Studies and International Relations Association (Insiera), 2026)
This study challenges the techno-optimist narrative regarding the transnational Muslim community by critically revisiting Peter Mandaville’s theory of Travelling Islam through a socio-epistemic lens. While early scholarship envisioned digital connectivity as a mechanism for the creative reimagining of the Umma, this research argues that the digital medium has engineered a condition identified as the Hollow Umma. Rather than facilitating a genuine democratization of knowledge, the digital sphere triggers a radical epistemological deregulation that actively replaces traditional Islamic meritocracy—anchored in scholarly lineage (Sanad) and qualified expertise (Ahl al-Dhikr)—with a democratic logic of quantity and virality. Furthermore, driven by the epistemic habits of Generation Z and their active reliance on social media as primary search engines, the locus of religious authority has drastically shifted from classical Ulama to